KOMUNIKASI PENDIDIKAN POLA KOMUNIKASI KYAI DAN SANTRI DI PONDOK PESANTREN - Yakin, Ario Ainal (Prophetica : Scientific and Research Journal of Islamic Communication and Broadcasting, 2017)
There is also the issue raised whether there is a pattern of communication between the Kyai and the santri themselves, this research itself is a qualitative research based on efforts to build their views which are examined in detail. Formed in words, a holistic picture is looking at something as an effort to build a detailed view of the research subject. Meanwhile, the research approach used is library research. Library research relies almost entirely on its data from libraries, so this research is more popularly known as descriptive qualitative research. In the learning process at Islamic boarding schools often use various forms or patterns of communication. Broadly speaking, there are four communication patterns used in Islamic boarding schools, namely primary, secondary, linear and circular communication